2016
DOI: 10.1111/jog.13227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two management protocols for postpartum hemorrhage during cesarean section in placenta previa: Balloon protocol versus non‐balloon protocol

Abstract: Application of the Bakri balloon for the management of PPH after CS in cases of PP is an effective strategy that should be affordable worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…In a series evaluating the use of IUBT in the management of placenta previa, the presence of accreta was associated with a failure rate of 83.3% (5/6); the odds ratio for success in the presence of accreta was as low as 0.001. 24 Our data concurred with such observations. Owing to the high failure rates…”
Section: Discussionsupporting
confidence: 92%
“…In a series evaluating the use of IUBT in the management of placenta previa, the presence of accreta was associated with a failure rate of 83.3% (5/6); the odds ratio for success in the presence of accreta was as low as 0.001. 24 Our data concurred with such observations. Owing to the high failure rates…”
Section: Discussionsupporting
confidence: 92%
“…The reasoning was that intrauterine balloon tamponade was an effective management of postoperative hemorrhage associated with placenta previa. In fact, some reports demonstrated that intrauterine balloon tamponade was effective in decreasing both intraoperative and postoperative hemorrhage [19,23,24]. In our institution, since March 2015, rapid insertion of intrauterine balloon tamponade has been performed to reduce hemorrhage after spontaneous separation of the placenta and has succeeded in reducing postoperative hemorrhage [25].…”
Section: Discussionmentioning
confidence: 94%
“…Without rapid and appropriate treatment, massive postoperative hemorrhage might induce adverse obstetrical outcomes including maternal death [22]. As a strategy for massive postoperative hemorrhage associated with placenta previa, previous studies demonstrated that intrauterine balloon tamponade was a useful technique to reduce the hemorrhage [23][24][25]. In these reports, the balloon was inserted after the massive postoperative hemorrhage had occurred [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without rapid and appropriate treatment, massive PPH might induce adverse obstetrical outcomes including maternal death [22]. As a strategy for massive PPH associated with placenta previa, previous studies demonstrated that intrauterine balloon tamponade was useful to decrease massive PPH [23][24][25]. In these reports, the timing of insertion of balloon was after massive PPH [23,24].…”
mentioning
confidence: 99%